MODEST FASHION ITANG YUNASZ DALAM FOTOGRAFI KOMERSIAL - Dhimo Kukuh Priyambodo (Specta: Journal of Photography, Arts, and Media, 2020)
The creation of the photographic work modest fashion Itang Yunasz in commercial photography will discuss how modest fashion Itang Yunasz is displayed in a visual that attracts consumers by highlighting the characteristics of clothing according to the target market. The object in the creation of this photographic work is a fashion label that is under the auspices of Itang Yunasz namely "Kamilla by Itang Yunasz", "Allea by Itang Yunasz", and "Itang Yunasz Ready To Wear". The results of the creation of this work of art, it was found that fashion photography requires a high budget, both in terms of models that must be professional, locations that must be prepared and accessories used to support photographed, because in the world of professional fashion work is needed in the seriousness of work. In addition, it was found the importance of harmonizing the theme of the clothes with the location to be used, so that between clothes and background will create a visual that appeals to market share.